Application of Information and Communication Technology (ICT) in Educational Administration: International Experiences and Vietnamese Policies - Nguyen, Linh Bang (Vietnam Journal of Education, 2023)
Information and Communication Technology (ICT) has become an integral part in educational programs across the globe. Despite its prominent benefits in education perceived by most educators and administrators, key challenges to ICT adoption in educational management still exist. This study aims to review international experiences in applying ICT in educational administration and related policies in Vietnam. The research results show that while perceptions of the importance of ICT application in educational administration are diverse, ICT application has significant impacts on educational administration. Moreover, ICT application is effective in educational management in both general and higher education. The study also identifies several challenges affecting ICT application. Additionally, policies in ICT application in educational administration in Vietnam are discussed. In conclusion, the research proposes several recommendations to have effective policies on the application of ICT in Vietnamese educational administration.